2016
DOI: 10.1080/07481187.2016.1271836
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of the Entre-os-Rios tragedy on grief and traumatic stress symptoms

Abstract: In 2001, in Entre-os-Rios, Portugal, a bridge fell on Douro River; all 59 passengers from 1 bus and 3 cars died and 36 bodies have never been recovered. The objective is to reveal the cumulative risk from multiple losses and unrecovered bodies, 10 years after, compared with grievers from road accidents. There are 2 groups of relatives of victims: from this tragedy (n = 20), with at least 1 unrecovered body; and from road traffic accidents (n = 20), with the same time after loss. The prevalence of prolonged gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…These results are consistent with the notion that bereavement in the context of disaster accentuates the stress reactions and defense mechanisms of grief, such as blaming oneself or others ( Johannesson et al, 2011 ; Kuo et al, 2003 ; Shultz et al, 2012 ). Injuries, witnessing people dying and the accumulation of losses (e.g., house, furniture, sources of income) have all been associated with the development of CG ( Cardoso et al, 2017 ; Ghaffari-Nejad et al, 2007 ; Johannesson et al, 2009 ; Hagl et al, 2015 ; Shultz et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with the notion that bereavement in the context of disaster accentuates the stress reactions and defense mechanisms of grief, such as blaming oneself or others ( Johannesson et al, 2011 ; Kuo et al, 2003 ; Shultz et al, 2012 ). Injuries, witnessing people dying and the accumulation of losses (e.g., house, furniture, sources of income) have all been associated with the development of CG ( Cardoso et al, 2017 ; Ghaffari-Nejad et al, 2007 ; Johannesson et al, 2009 ; Hagl et al, 2015 ; Shultz et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to natural disasters, those of a technological nature have long-lasting consequences on psychological health ( Bromet et al, 2011 ; Chung & Kim, 2010 ; Morgan & Bhugra, 2010 ). The prevalence of CG in a post-disaster context varies, ranging from 10% to 20% ( Rynearson et al, 2002 ) and up to 95% of bereaved people ( Cardoso et al, 2017 ; Djelantik et al, 2020 ). Complicated grief in the context of train accidents has received little attention: in the 39 studies focused on grief in the wake of a disaster ( Maltais et al, 2020 ), only one concerned a train derailment ( Sigh & Raphael, 1981 ).…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, the studies with the highest number of bereaved individuals or studies providing the most relevant data were included. The characteristics of all 25 included studies can be found in Table 2 (Bartik, Maple, Edwards, & Kiernan, 2013;Cardoso et al, 2017;Dyregrov, Dyregrov, & Kristensen, 2015;Dyregrov et al, 2003;Harms et al, 2015;Hu et al, 2015;Kristensen, Heir, Herlofsen, Langsrud, & Weisaeth, 2012;Kristensen, Weisaeth, Hussain, & Heir, 2015;J. Li, Chow, Shi, & Chan, 2015;McDevitt-Murphy, Neimeyer, Burke, Williams, & Lawson, 2012;Mitchell, Kim, Prigerson, & Mortimer-Stephens, 2004;Morina & Emmelkamp, 2012;Morina, Rudari, Bleichhardt, & Prigerson, 2010;Morina, Von Lersner, & Prigerson, 2011;Neria et al, 2007;Prigerson, Bridge, et al, 1999;Schaal, Elbert, & Neuner, 2009;Shear, Jackson, Essock, Donahue, & Felton, 2006;Spooren, Henderick, & Jannes, 2001;Stammel et al, 2013;Tsutsui, Hasegawa, Hiraga, Ishiki, & Asukai, 2014;van Denderen, de Keijser, Huisman, & Boelen, 2016;Williams & Rheingold, 2015;Xu, Herrman, Bentley, Tsutsumi, & Fisher, 2014;Yun, Huh, Han, Huh, & Chae, 2018).…”
Section: Search Resultsmentioning
confidence: 99%
“…Most studies assessing psychopathology following unnatural losses have been carried out after specific events such as a large accident, e.g., Cardoso, Ferreira, Rocha, Leite, and Almeida (2017), a natural disaster, e.g., Hu, Li, Dou, and Li (2015), or a specific terrorism incident, e.g., Neria et al (2007). If we were able to investigate the differences and similarities of prevalence rates and loss-related characteristics between studies assessing PGD following unnatural losses in a metaanalysis, we might be able to identify vulnerable groups of bereaved individuals.…”
Section: Consequences Of Traumatic Lossmentioning
confidence: 99%
See 1 more Smart Citation